U–Pb Dating and Hf Isotopes Analysis of Detrital Zircons of the Shanxi Formation in the Otuokeqi Area, Northwestern Ordos Basin. (26th February 2021) - Song, Jiaxuan; Gong, Hujun; Yao, Jingli; Zhao, Huitao; Zhao, Xiaohui; Zhang, Yunxiang; Chen, Biao
Abstract : The Paleozoic strata are widely distributed in the northwest of the Ordos Basin, and the provenance attributes of the basin sediments during this period are still controversial. In this paper, the detrital zircon LA-MC-ICPMS U-Pb age test was conducted on the drilling core samples of the Shanxi Formation of the Upper Paleozoic in the Otuokeqi area of the Ordos Basin, and the provenance age and the characteristic of the Shanxi formation in the Otuokeqi area in the northwest were discussed. The cathodoluminescence image shows that the detrital zircon has a clear core-edge structure, and most of the cores have clear oscillatory zonings, which suggests that they are magmatic in origin. Zircons have no oscillatory zoning structure that shows the cause of metamorphism. The age of detrital zircon is dominated by Paleoproterozoic and can be divided into four groups, which are 2500 2300 Ma, 2100 1600 Ma, 470 400 Ma, and 360 260 Ma. The first two groups are the specific manifestations of the Precambrian Fuping Movement (2.5 billion years) and the Luliang Movement (1.8 billion years) of the North China Craton. The third and fourth groups of detrital zircons mainly come from Paleozoic magmatic rocks formed by the subduction and collision of the Siberian plate and the North China plate. The ε Hf t value of zircon ranges from -18.36 to 4.33, and the age of the second-order Hf model T DM 2 ranges from 2491 to 1175 Ma. The source rock reflecting the provenance of the sediments comes from the material recycling of the Paleoproterozoic and Mesoproterozoic in the crust, combined with the Meso-Neoproterozoic detrital zircons discovered this time, indicating that the provenance area has experienced Greenwellian orogeny.